+0  
 
0
202
2
avatar
Guest Dec 19, 2014

Best Answer 

 #2
avatar+91482 
+10

-x+y=6

A really easy way to think about this is that 

The equation of the y axis is x=0  sub in x=0 and solve for y  straight away you can see that y=6    [-0+y=6]

The equation of the x axis is y=0  sub in y=0 and solve for x  [-x+0=6]      so x=-6

Melody  Dec 19, 2014
Sort: 

2+0 Answers

 #1
avatar+958 
+10

Hello, it's me again!

 

Once again, isolate 'y' to make it into y = mx + b form.

 

-x + y = -6

y = x - 6

 

Your y-intercept is -6.

 

Now, flip flop the equation and solve for 'x'. Once you have it in the x = my + b form, 'b' is the x intercept.

 

-x + y = -6

-x = -y - 6

x = y + 6

 

Your x-intercept is 6.

GoldenLeaf  Dec 19, 2014
 #2
avatar+91482 
+10
Best Answer

-x+y=6

A really easy way to think about this is that 

The equation of the y axis is x=0  sub in x=0 and solve for y  straight away you can see that y=6    [-0+y=6]

The equation of the x axis is y=0  sub in y=0 and solve for x  [-x+0=6]      so x=-6

Melody  Dec 19, 2014

28 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details